Do I have to go to school? : a first look at starting school - Thomas ,Pat; Harker , Lesley (London Wayland, 2023)
An illustrated picture book for children who are starting school for the first time. Going to school is a huge change for young children, this book encourages children to discover the joy of learning new things, meeting new people and having new experiences. Notes for parents and teachers at the back of the book provide valuable advice for how to share this book with your child or class"--Publisher's descriptiond or class
Education
Keywords: Children's stories; Essais fictionnels